Pengaturan Hukum Teknologi Blockchain Dan Penerapannya Dalam Transaksi Bisnis Di Indonesia - Salsabilla .; Engrina Fauzi (CV. ITTC INDONESIA, 2026)
The Disruption Era, also known as the 5.0 Revolution, is directing the world toward a new phase that encompasses various aspects of life, one of the most significant being the economic sector. Developments in the economy during this era are synergistically linked with technological advances and the accessibility of legal enforcement. This research aims to evaluate the challenges in implementing blockchain in Indonesia, particularly in technical and regulatory aspects. It also identifies potential legal risks arising from the use of blockchain technology without adequate regulation. This study employs a normative juridical method, which examines law from a normative perspective, viewing it as a set of rules written in legislation, legal doctrines, and court decisions. One of the economic developments in the disruption era is the emergence of new payment methods in business transactions. Traditionally, transactions have been conducted using conventional currency; however, with the rise of digitalization, business transactions are shifting to the internet-based digital realm. Blockchain technology facilitates and expands applications in various sectors such as digital currencies, logistics, and voting systems. Its use demands strict regulations to ensure secure, trustworthy, and legally compliant implementation. To provide legal certainty and protection in cryptocurrency transactions, the Indonesian government has issued policies to safeguard crypto asset holders. These policies are embodied in Law Number 10 of 2011, which amends Law Number 32 of 1997 on Commodity Futures Trading. Based on the analysis, the author recommends that lawmakers immediately formulate specific and comprehensive regulations regarding blockchain technology. This is due to the urgent need for legal arrangements that are not only sectoral but also integrative across various legal domains, including the legal recognition of blockchain-based transactions, smart contracts, and the decentralized management and accountability of data. Second, overlaps and legal gaps in existing regulations — such as the Electronic Information and Transactions Law, the Personal Data Protection Law, the Currency Law, and the Government Regulation on the Implementation of Electronic Systems and Transactions — must be harmonized. Adjustments should reflect the distinctive characteristics of blockchain technology, including its immutability, transparency, and lack of central authority, to ensure the national legal system can effectively address digital era challenges. Regarding legal protection for users of blockchain technology in cryptocurrency and business transactions, the author proposes the establishment of a specific, integrated regulatory framework that governs the use of blockchain and crypto assets as part of a growing digital ecosystem. This regulation should contain clear provisions on consumer protection, technological standards, data security, and the responsibilities of business actors. Finally, during the transition of supervisory authority from Bappebti to the Financial Services Authority (OJK), the government must ensure that OJK is equipped with the capacity, infrastructure, and legal framework necessary for effective oversight of digital asset trading.